2008
DOI: 10.1016/j.jcrysgro.2008.04.034
|View full text |Cite
|
Sign up to set email alerts
|

X-ray topography of Ca0.5Sr0.5NdAlO4 single crystal

Abstract: a b s t r a c tA Ca 0.5 Sr 0.5 NdAlO 4 single crystal grown by the Czochralski method in the [1 0 0] direction was investigated by means of conventional projection X-ray topography, and by means of synchrotron white beam and monochromatic beam topography.The topographic investigation revealed growth striations with strong black diffraction contrasts distributed periodically in the form of concentric rings, and a significant number of resolved defects. Some of these defects seem to be associated with precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
(18 reference statements)
1
4
0
Order By: Relevance
“…1a). The same result was observed for another samples studied earlier [8][9][10][11][12][13][14][15]. In the outer part of these crystals a lot of linear black diffraction contrasts and volume defects contrasts of irregular shapes were observed.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…1a). The same result was observed for another samples studied earlier [8][9][10][11][12][13][14][15]. In the outer part of these crystals a lot of linear black diffraction contrasts and volume defects contrasts of irregular shapes were observed.…”
Section: Resultssupporting
confidence: 85%
“…The results of our previous studies concerning SLG crystals were shown in Refs. [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The synchrotron investigation can reveal signicant strains associated with the segregation fringes [42]. In particular they can be revealed in transmission and reection section topography, similarly as it was discussed in [47].…”
Section: Revealing Of the Segregation Fringes And Defects Related To mentioning
confidence: 65%
“…Synchrotron radiation white beam back reection projection topograph in 134 reection, λ = 0.094 nm; E denotes boundary between two slightly misoriented regions and G, H defect groups with two kinds of diraction contrasts. According to A. Malinowska et al[42].partly related with growth striations. The zebra pattern (Fig.…”
mentioning
confidence: 99%
“…Density of the fringes are dierent in both crystals. Detailed studies of the lattice deformation associated with the segregation fringes were performed by means of synchrotron topography and is presented in [33,36]. (010) and (011) lattice planes with the sample surface.…”
Section: The Czochralski Grown Oxide Materialsmentioning
confidence: 99%